2011
DOI: 10.1007/s10549-011-1869-4
|View full text |Cite
|
Sign up to set email alerts
|

Case report and review of the literature: Secretory breast cancer in a 13-year-old boy—10 years of follow up

Abstract: Carcinoma of the breast is very rare in childhood, accounting for less than 1% of all childhood malignancies and is especially rare in boys. Delay in diagnosis and treatment in children with breast cancer may occur because surgeons are very reluctant to perform biopsies on the developing breast, since these can cause future deformity. We report a case of male secretory breast carcinoma in a 13-year-old boy. Radical mastectomy was performed followed by chemotherapy. The patient is free of disease after 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 36 publications
(94 reference statements)
0
24
0
3
Order By: Relevance
“…SBC is also known to occur in both sexes with prior literature showing a male to female ratio of 1:6 [6], our review of the NCDB demonstrated a ratio of 1:31. Multiple case reports have been reported in the literature [7,[8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…SBC is also known to occur in both sexes with prior literature showing a male to female ratio of 1:6 [6], our review of the NCDB demonstrated a ratio of 1:31. Multiple case reports have been reported in the literature [7,[8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…As a low-grade carcinoma, SCB has an indolent course and good long-term survival. The prognosis is generally considered to be better in children and adolescents, relatively poor in adults, and distant metastasis is rarely observed (32,33). Axillary lymph node involvement has been reported in 30% of the cases (33), particularly those with primary tumors > 2 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Secretory breast carcinoma can present at any age, in both males and females, with a ratio of approximately 1:2 (Table ) to 1:6 . The primary tumor commonly presents as a slow growing, painless, mobile, palpable well‐circumscribed mass located in the left and right breast with equal frequency .…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…There are reports of using systemic therapy, but this should be discouraged based on the indolent prognosis, nonresponsiveness, and low metastatic risk of these tumors . There have been no documented reports showing added benefit of adjuvant chemotherapy and therefore is no evidence for its role in treatment .…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation